Effects of stingless bee (Heterotrigona itama) pollination on greenhouse cucumber (Cucumis sativus) - Wahizatul Afzan Azmi; Nurhidayah Samsuri; Muhammad Firdaus Mohd. Hatta; Roziah Ghazi; Chuah, Tse Seng (Penerbit Universiti Kebangsaan Malaysia, 2017)
Stingless bee is one of the important pollinators in open field crops as well as in the greenhouse crops. However, the potential use of stingless bees as pollinator for greenhouse cucumber is less documented in Malaysia. In this study, the stingless bees, Heterotrigona itama were placed together with the greenhouse cucumbers, Cucumis sativus in order to investigate the effects of H. itama pollination on greenhouse cucumber. This experiment involved three pollination treatments; namely pollination without stingless bee, hand-cross pollination and pollination by stingless bee, H. itama. Two hives of stingless bees were introduced into the greenhouse at least two days before the cucumber flowers started to bloom. Results showed that the cucumbers pollinated by stingless bee and hand-cross pollination produced heavier, longer and larger cucumbers compared to those produced from pollination without stingless bees. However, in terms of dried weight seed, firmness and colour of cucumbers, no significant difference between the treatments were detected. Further study is required in order to determine the pollination efficiency of stingless bees in greenhouse crops.